Synthesis of Graphene Oxide/Corn Cob Composites and investigation of their adsorption performance of Dye. (November 2020) - Qu, Yanping; Kang, Song; Sun, Jingjing; Zhang, Ling; Sun, Junqing; Yang, Shaoliang; Yang, Jinghui
Abstract: Corncob and Graphene oxide were used to prepare and characterize corncob/graphene oxide (GO/CC) composites. The adsorption performance of GO/CC on dye wastewater was studied, and the factors affecting the adsorption effect were investigated. The results showed that GO/CC had rich functional groups which could provide sufficient binding sites for Congo red. It could remove Congo red solution strongly, and the removal rate was as high as 80%. GO/SP was endothermic in the process of Congo red adsorption. The reaction was mainly based on chemical adsorption.